Predictive Modeling of Functional and Physical Properties of Extrusion Cooked Ready-To-Eat Corn Meal - Adeyemi Adio Aderele; Adewumi Babatunde; Adeniyi Olayanju; Adekojo Waheed (University of Sultan Ageng Tirtayasa, 2025)
Cornmeal is the product of corn-based food processed or pre-cooked through extrusion to produce a ready-to-eat breakfast. The quality of the meal depends on the extrusion cooking factors and process variables. The study focused on the effects of screw speed (SS: 100-120 rpm), barrel temperature (BT: 170-190℃), feed rate (FR: 40-60 rpm), and moisture content (MC: 20-25%) on: water absorption index (WAI), water solubility index (WSI), bulk density (BD) and expansion ratio (ER) to predict functional and physical properties of extruded corn meal. Brabender single-screw laboratory-scale extruder was used to process corn flour into ready-to-eat corn meal. JMP Pro 16 was used for experimental design, which was conducted in triplicate using: Central composite response surface methodology. Design Expert 13 and MATLAB 2020b were used respectively for data analysis and visualization. The main, interaction and quadratic effects of SS, BT, FR, and MC were evaluated on WAI, WSI, BD and ER. The significance level was established at p≤0.05. A second-degree polynomial equation was fitted for each response variable as a function of extrusion cooking process factors. Adequate precision/R-Square values for WAI, WSI, BD, and ER respectively were 25.92/0.97, 11.69/0.99, 10.00/0.94, and 22.51/0.99, which measured each model’s degree of fitness. These values proved that each model have good predictability and was fitted for prediction purposes.